2010
DOI: 10.1007/s12010-010-9080-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess Optimization of Furanocoumarin Elicitation by Medium Renewal and Re-elicitation: A Perfusion-Based Approach

Abstract: Effect of various abiotic (methyl jasmonate, salicylic acid) and biotic (yeast extract, Aspergillus niger) elicitors on furanocoumarin production and in situ product removal was studied using shoot cultures of Ruta graveolens L. Elicitation by yeast extract (1% w/v) on day 15 was most effective. It led to 7.8-fold higher furanocoumarin production that was attained 24 h after elicitation and 43% of the product was released into the medium. Changes in the relative concentration of furanocoumarins produced depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…SA is generally produced in plants and accumulated at pathogen attack sites, and then spreads to several plant parts triggering the biosynthetic pathway for accumulation of secondary metabolite production [45]. This is an agreement with Diwan and Malpathak [41] and Coste et al [34] who reported that 200 µM SA increased the furanocoumarin production in Rutagraveolens shoot cultures and hypericin and pseudohypericin content in Hypericum maculatum shoot cultures. However, 50 µM SA signi cantly reduced the diosgenin accumulation in micro-tubers of Chlorophytum borivilianum [46].…”
Section: Effect Of Elicitors On Diosgenin Production In Ddeltoidea Ssupporting
confidence: 71%
“…SA is generally produced in plants and accumulated at pathogen attack sites, and then spreads to several plant parts triggering the biosynthetic pathway for accumulation of secondary metabolite production [45]. This is an agreement with Diwan and Malpathak [41] and Coste et al [34] who reported that 200 µM SA increased the furanocoumarin production in Rutagraveolens shoot cultures and hypericin and pseudohypericin content in Hypericum maculatum shoot cultures. However, 50 µM SA signi cantly reduced the diosgenin accumulation in micro-tubers of Chlorophytum borivilianum [46].…”
Section: Effect Of Elicitors On Diosgenin Production In Ddeltoidea Ssupporting
confidence: 71%
“…Furthermore, elicitation of C. maculatum plants with copper(II) chloride (10 mM The differential accumulation of furanocoumarins in the medium or the cells after elicitation with various elicitors is unexpected, but not completely unprecedented. Furanocoumarins are also released into the medium after elicitation by Ruta graveolens (Diwan and Malpathak 2011) and Glehnia littoralis (Ishikawa et al 2009). Diwan and Malpathak (2011) reported that in their elicitation system the amount of furanocoumarins is dependent on the elicitor, the most efficient being yeast extract.…”
Section: Discussionmentioning
confidence: 99%
“…Furanocoumarins are also released into the medium after elicitation by Ruta graveolens (Diwan and Malpathak 2011) and Glehnia littoralis (Ishikawa et al 2009). Diwan and Malpathak (2011) reported that in their elicitation system the amount of furanocoumarins is dependent on the elicitor, the most efficient being yeast extract. In our system biotic compounds (alginic acid, cellulase and chitosan) were also the most efficient.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that elicitor used and its concentrations play an important role on the effectiveness of elicitation. In previous studies, it was reported that MeJa has increased furanocoumarin production in Ruta graveleons shoot cultures and asiaticoside production in Centella asiatica whole plant culture [41,36]. Mendoza et al [28] reported that elicitation with 3 µM MeJa increased phenolics and avonoids content in Thevetia peruviana suspension cultures.…”
Section: Discussionmentioning
confidence: 98%